Recención libro "Law and revolution. The Formation of The Western Legal Tradition", de Harold J. Berman - Arnello Romo, Mario (Revista Tribuna Internacional, 2012)
Comentario del Profesor Mario Arnello al libro ""Law and revolution. The Formation of The Western Legal Tradition", de Harold J. Berman, Profesor Emérito de Harvard Law School, B.A. Darmouth College, 1938; M.A.1942, LL.B. 1947, Yale University; LL.D. Catholic University of America, 1991; D.H.L. Virginia Theological Seminary, 1995; Doctor honoris causa, University of Ghent, 1997; Doctor honoris causa, Russian Academy of Sciences Law University, 2000.